Auxin and Its Interaction With Ethylene Control Adventitious Root Formation and Development in Apple Rootstock - Bai, Tuanhui; Dong, Zhidan; Zheng, Xianbo; Song, Shangwei; Jiao, Jian; Wang, Miaomiao; Song, Chunhui (Frontiers in Plant Science, 2020)
Adventitious root (AR) formation is indispensable for vegetative asexual propagation. Indole-3-butyric acid (IBA) functioned indirectly as precursor of IAA in regulating AR formation. Ethylene affects auxin synthesis, transport, and/or signaling processes. However, the interactions between auxin and ethylene that control AR formation in apple have not been elucidated. In this study, we investigated the effects of IBA and its interaction with ethylene on AR development in apple. The results revealed that IBA stimulated the formation of root primordia, increased the number of AR, and upregulated expression of genes (MdWOX11, MdLBD16, and MdLBD29) involved in AR formation. Comparison of different periods of IBA application indicated IBA was necessary for root primordium formation, while long time IBA treatment obviously inhibited root elongation. RNA-seq analysis revealed that many plant hormone metabolism and signal transduction related genes were differentially expressed. IBA stimulated the production of ethylene during AR formation. Auxin inhibiting adventitious roots elongation depended on ethylene. Together, our results suggest that the inhibitory role of auxin on AR elongation in apples is partially mediated by stimulated ethylene production.